Long-term remission in multiply relapsed enteropathy-associated T-cell lymphoma following CD30 CAR T-cell therapy - Voorhees, Timothy J. (Blood Adv, 2020)
CD30 CAR T-cell therapy promoted a prolonged remission in a patient with multiply relapsed EATL.